Career Development dan Kompensasi Terhadap Kepuasan Kerja dengan Work Motivation sebagai Variabel Moderating - Junita Safitri; Rizky Ananda Putry (Universitas Harapan Medan, 2022)
This study aims to determine career development, compensation, and work motivation to moderate the influence of career development and compensation on job satisfaction at the Honda Arista Medan. The sample used in this study was 113 employees service at the Honda Arista Medan using saturated samples. The analysis technique used in this research is the Interaction Test (Moderated Regression Analysis). The results of this study indicate that career development has a positive and significant effect on job satisfaction at Honda Arista Medan. Compensation positively and significantly affects job satisfaction at the Honda Arista Medan. Work motivation that moderates career development has a positive and significant effect on job satisfaction at Honda Arista Medan. And work motivation that moderates compensation has a positive and significant effect on job satisfaction at Honda Arista Medan. The value of Adjusted R Square is 0.540. This means that 54.0% of the variation in job satisfaction scores can be influenced by the role of career development and compensation. So it can be concluded that the influence of career development and compensation can affect job satisfaction by 54.0% and the remaining 46.0% is influenced by other variables.